Measuring the Sense of Agency: A French Adaptation and Validation of the Sense of Agency Scale (F-SoAS) - Hurault, Jean-Christophe; Broc, Guillaume; Crône, Lola; Tedesco, Adrien; Brunel, Lionel (Frontiers in Psychology, 2020)
Sense of Agency (SoA) is the subject of growing attention. It corresponds to the capacity to claim authorship over an action, associate specific consequences with a specific action, and it has been claimed to be a key point in the development of consciousness. It can be measured using the Sense of Agency Scale (SoAS), originally proposed by Tapal et al. (2017), who distinguished it into two-factor: Sense of Positive Agency (SoPA) and Sense of Negative Agency (SoNA). This study reports on the first adaptation of the SoAS into another language, French. For this French version of the Sense of Agency Scale (F-SoAS), we analyzed responses from a sample of 517 native French-speakers. Our results indicate that the scale has good psychometric properties. Factor analysis confirm the same two-factor model as Tapal et al. (2017). However, some items were removed due to insufficient loadings with factors, leading to a short version of the scale (7-item). Furthermore, we observed gender differences that are consistent with findings in the literature. Specifically, women report higher SoNA scores and lower SoPA scores than men. We conclude by discussing possible uses and future directions for the scale.